Xiao-Chai-Hu-Tang (XCHT) Intervening Irinotecan’s Disposition: The Potential of XCHT in Alleviating Irinotecan-Induced Diarrhea - Sun, Rongjin; Basu, Sumit; Zeng, Min; Sunsong, Robin; Li, Li; Ghose, Romi; Wang, Wei; Liu, Zhongqiu; Hu, Ming; Gao, Song (Current Cancer Drug Targets, 2019)
Background: Diarrhea is a severe side effect of irinotecan, a pro-drug of SN-38 used for the treatment of many types of cancers. Pre-clinical and clinical studies showed that decreasing the colonic exposure of SN-38 can mitigate irinotecan-induced diarrhea. Objective: The purpose of this study is to evaluate the anti-diarrhea potential of Xiao-Chai-Hu-Tang (XCHT), a traditional Chinese herbal formula, against irinotecan-induced diarrhea by determining if and how XCHT alters the disposition of SN-38. Methods: LC-MS/MS was used to quantify the concentrations of irinotecan and its major metabolites (i.e., SN-38, SN-38G). An Intestinal perfusion model was used to determine the effect of XCHT on the biliary and intestinal secretions of irinotecan, SN-38, and SN-38G. Pharmacokinetic (PK) studies were performed to determine the impact of XCHT on the blood and fecal concentrations of irinotecan, SN-38, and SN-38G. Results: The results showed that XCHT significantly inhibits both biliary and intestinal excretions of irinotecan, SN-38, and SN-38G (range: 35% to 95%). PK studies revealed that the fecal concentrations of irinotecan and SN-38 were significantly decreased from 818.35 ± 120.2 to 411.74 ± 138.83 μg/g or from 423.95 ± 76.44 to 245.63 ± 56.72 μg/g (p<0.05) by XCHT, respectively, suggesting the colonic exposure of SN-38 is significantly decreased by XCHT. PK studies also showed that the plasma concentrations of irinotecan, SN-38, and SN-38G were not affected by XCHT. Conclusion: In conclusion, XCHT significantly decreased the exposure of SN-38 in the gut without affecting its plasma level, thereby possessing the potential of alleviating irinotecan-induced diarrhea without negatively impacting its therapeutic efficacy.
Keywords: Irinotecan